AHP DENGAN MATRIKS PREFERENSI DALAM ALJABAR MAX-PLUS - I Gusti Ngurah Rai Usadha (UNEJ e-Proceeding, 2022)
Analytical Hierarchy Process (AHP) is a decision-making method to determine the best alternative from a number of alternatives based on certain criteria. One of the fundamental problems in AHP is how to obtain a preference matrix for a number of alternatives. In this paper, a preference matrix is formed so that it meets certain conditions in Tropical Algebra. Furthermore, the maxplus operation is applied to obtain the eigenvectors of the preference matrix that describes the steady state condition. A case study was conducted on determining the priority of road maintenance in Bangkalan Regency. The calculation results show that there is a conformity with the results of previous studies. Keywords: Analytical Hierarchy Process, preference matrix, eigenvectors, steady state.